Values in Lutheran Social Teaching v. Rights in Dobbs - Streufert, Mary J. (Dialog, 2025)
The reasoning of the court in what is called “the Dobbs decision” is rooted in rights related to the 14th Amendment of the US Constitution. A problem from a Lutheran perspective is that the context for the court's majority decision about rights is rooted in a heritage of patriarchy and white supremacy. The values of patriarchy and white supremacy are hierarchy and control, particularly of bodies and reproduction. The result is that Dobbs reinforces limited moral agency and primarily prioritizes flourishing of embryos and fetuses without asking what pregnant neighbors need. The social teaching of the Evangelical Lutheran Church in America (ELCA) stands against the Dobbs decision.